Remote Ischemic Conditioning in Cerebral Diseases and Neurointerventional Procedures: Recent Research Progress - Zhou, Geng; Li, Ming Hua; Tudor, Gabriel; Lu, Hai Tao; Kadirvel, Ramanathan; Kallmes, David (Frontiers in Neurology, 2018)
Abstract Cardiovascular accidents are increasing in prevalence and are among the leading causes of morbidity and mortality in both developed and developing countries. Despite the progress in endovascular treatment, ischemia/reperfusion (IR) injury is an important contributor to post-surgical mortality and morbidity affecting a wide range of neurointerventional procedures. However, pharmacological recruitment of effective cerebral protective signaling has been largely disappointing to date. In remote ischemic conditioning (RIC), repetitive transient mechanical obstruction of vessels at a limb remote from the IR injury site protects vital organs from IR injury and confers infarction size reduction following prolonged arterial occlusion. Results of pharmacologic agents appear to be species-specific, while RIC is based on the neuroprotective influences of phosphorylated Akt, signaling proteins, nitric oxide, and transcriptional activators, the benefits of which have been confirmed in all species. Inducing RIC protection in patients undergoing cerebral vascular surgery or those who are at high risk of brain injury has been the subject of research and has been enacted in clinical settings. Its simplicity and noninvasive nature, as well as the flexibility of the timing of RIC stimulus, also makes it feasible to apply alongside neurointerventional procedures. Furthermore, despite nonuniform RIC protocols, emerging literature demonstrates improved clinical outcomes. The aims of this article are: to summarize the potential mechanisms underlying different forms of conditioning, to explore the current translation of this paradigm from laboratory to neurovascular diseases, and to outline applications for patient care.